Incubadora social: um estudo da escola empreendedora de corte e costura da Fundação Jari - Moraes, Erika Campanharo de (2015)
Micro and small businesses as well as individual micro-entrepreneurs are important for job creation and economic dynamism. Studies show that these businesses, when created and/or developed in business incubators, survive longer in the market than those that are created and developed alone. In this context, the company incubators stand out as important organizations for the whole society. There are several modes of operation, and one of them includes the development of businesses called inclusive, social and/or with social impact. The aim of this study was to analyze the performance of a social incubator that develops inclusive business through its activities, results and social impacts, by means of the perception of the incubator coordinator and entrepreneurs that have been incubated. To achieve this objective, a qualitative empirical research was made with a social incubator called Escola Empreendedora da Fundação Jari. From the case study of this work, it was found that social incubators have similar practices of technology and traditional base companies´ incubators, but also adopt other practices to better meet the needs of your target audience. Among other practices, can be highlighted: the phase of pre-incubation, corresponding to a training and preparation prior to entry into the incubator, and income generation at the beginning stage of incubation, since the income is needed to keep participants in the project by providing basic needs. The Social Incubator of Escola Empreendedora de Corte e Costura da Fundação Jari has shown itself to be an important organization for the integration of people in disadvantaged conditions in the production chain. The first incubation cycle enabled four women to undertake their own businesses, and one of them is no longer dependent on a government welfare program. In addition, the incubator could also be recognized for facilitating the entry of people into the labor market, during the training phase of pre-incubation and even during incubation, in which the professionals had the opportunity to gain experience by means of a corporate internship. Therefore, the incubator developed business and attracted experienced workers to the labor market. Therefore, this study is relevant as contributing to the debate about the role of social incubators